2008
DOI: 10.1186/gb-2008-9-5-r86
|View full text |Cite
|
Sign up to set email alerts
|

GeneCount: genome-wide calculation of absolute tumor DNA copy numbers from array comparative genomic hybridization data

Abstract: Absolute tumor DNA copy numbers can currently be achieved only on a single gene basis by using fluorescence in situ hybridization (FISH). We present GeneCount, a method for genome-wide calculation of absolute copy numbers from clinical array comparative genomic hybridization data. The tumor cell fraction is reliably estimated in the model. Data consistent with FISH results are achieved. We demonstrate significant improvements over existing methods for exploring gene dosages and intratumor copy number heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…In line with Nancarrow and colleagues (34) For accurate estimates of the allelic states of CNAs in FFPE aneuploid tumors, we showed that integration of the DNA index in conjunction with SNP arrays (8,27) is crucial. Otherwise, most, if not all, CNAs will be misinterpreted, which is also supported by the findings of Lyng and coworkers on aCGH (16). For example, the patterns of CNAs on chromosomes 8 and 18 of the near-diploid and the aneuploid fractions of case 5 seem to be identical, but their allelic states are shown to differ after integration of the DNA index (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In line with Nancarrow and colleagues (34) For accurate estimates of the allelic states of CNAs in FFPE aneuploid tumors, we showed that integration of the DNA index in conjunction with SNP arrays (8,27) is crucial. Otherwise, most, if not all, CNAs will be misinterpreted, which is also supported by the findings of Lyng and coworkers on aCGH (16). For example, the patterns of CNAs on chromosomes 8 and 18 of the near-diploid and the aneuploid fractions of case 5 seem to be identical, but their allelic states are shown to differ after integration of the DNA index (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…These differences also show that intratumor heterogeneity is more extensive than is generally observed by ploidy and LAIR analysis because both techniques register the dominant clone(s). Intratumor heterogeneity has also been identified by aCGH (16). However, LAIR analysis has increased value relative to classical methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies aim to bring these effects into the equation (22,23), these difficulties still remain today. In addition to these limitations, array-CGH provides no information regarding which of the two alternative alleles has been gained or lost, and it overlooks copy numberneutral aberrations.…”
Section: −3mentioning
confidence: 99%
“…Absolute DNA copy numbers were calculated from the aCGH ratios by the GeneCount algorithm, and were corrected for tumor ploidy, as determined by flow cytometry, and normal cell fraction of the samples35 . Samples showing two distinct G 1 peaks in the DNA histogram by flow cytometry were classified as aneuploid, and the ploidy was determined from the position of the G 1 peak of the aneuploid cells relative to the corresponding peak of the diploid cells.…”
mentioning
confidence: 99%